THE FUNCTION OF THE PUBLIC SQUARES IN THE URBAN ENVIRONMENT:THE CASE OF SPORTS SQUARE BELMAR FIDALGO FROM CAMPO GRANDE (Fiep Bulletin - online, 2014)
Considered as a means of recreation, the square aims to provide people not only a place for leisure, but also for quality of life, prevention of diseases, and also as a form of socialization.This article aims to make an analysis of current situation of Belmar Plaza Hidalgo in the city of Campo Grande-MS, to evaluate their characteristics and use. So we can address the function of public squares in the urban environment, it is necessary, we also urban quality of life. The squares as public space, play important roles in the urban environment, including the integration of the community and the improvement of environmental quality. Today, it is observed that the squares are no longer enjoyed as in times past. The squares have contributed to respect for the environment and heritage, as well as assist in the control of solar radiation, air humidity and wind action. What you realize is that a construction of nature built on squares we can confirm if the square of the Belmar Fidalgo.
Keywords: public squares; mode of use; quality of life.